Pomiar zależności między zjawiskami mierzonymi na różnych poziomach agregacji przestrzennej - Biskup, Dariusz (Measuring Relationships Among Phenomena Measured on Various Levels of Spatial Aggregation, 2008)
The paper describes the problem of spatial data measured at disparate resolutions. One set of data is point-referenced and the other is areal. The problem of reconciliation of these types of data is illustrated with the measurement of the correlation coefficient between environmental pollution and cancer rates. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 6, s. 76-94